On the Association of Cash Flow Variables with Market Risk: Further Evidence. - Ismail, Badr E.; Kim, Moon K. (The Accounting Review, 1989)
ABSTRACT: The purpose of this study is to determine whether funds and cash flows possess incremental information beyond accrual earnings in the context of explaining market risk. The results indicate that funds and cash flow risk measures (betas) provide significant incremental explanatory power over that provided by the earnings risk measure (β) in explaining the variability in market betas. Additionally, the results reveal that an earnings β does not possess additional explanatory power beyond that provided by either funds or cash flow betas. The major implication of the results is that with respect to the explanation of market risk, the information in accrual earnings appears to be a subset of the broader set of information contained in cash flows.